Dehydrated Carbon Coupled with Laser-Induced Breakdown Spectrometry (LIBS) for the Determination of Heavy Metals in Solutions. Issue 10 (October 2015) - Niu, Guanghui; Shi, Qi; Xu, Mingjun; Lai, Hongjun; Lin, Qingyu; Liu, Kunping; Duan, Yixiang
In this article, a novel and alternative method of laser-induced breakdown spectroscopy (LIBS) analysis for liquid sample is proposed, which involves the removal of metal ions from a liquid to a solid substrate using a cost-efficient adsorbent, dehydrated carbon, obtained using a dehydration reaction. Using this new technique, researchers can detect trace metal ions in solutions qualitatively and quantitatively, and the drawbacks of performing liquid analysis using LIBS can be avoided because the analysis is performed on a solid surface. To achieve better performance using this technique, we considered parameters potentially influencing both adsorption performance and LIBS analysis. The calibration curves were evaluated, and the limits of detection obtained for Cu 2+, Pb 2+, and Cr 3+ were 0.77, 0.065, and 0.46 mg/L, respectively, which are better than those in the previous studies. In addition, compared to other absorbents, the adsorbent used in this technique is much cheaper in cost, easier to obtain, and has fewer or no other elements other than C, H, and O that could result in spectral interference during analysis. We also used the recommended method to analyze spiked samples, obtaining satisfactory results. Thus, this new technique is helpful and promising for use in wastewater analysis and management.